2012
DOI: 10.5296/ijafr.v2i2.2065
|View full text |Cite
|
Sign up to set email alerts
|

Audit Quality and Earnings Management in the Tunisian Context

Abstract: In this study, we test the effect of the implementation of the financial security law (n° 2005-96) and the audit quality (Big 4 auditors, auditor industry specialization and audit tenure) on constraining the extent of real and accruals based earnings management in the Tunisian context. Using 319 firm-year observations during the period 2000-2010, our results suggest that auditor industry specialization and Big 4 auditors associated with lower levels of accruals earnings management. We also find that the Big … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 45 publications
(94 reference statements)
5
15
0
16
Order By: Relevance
“…While some empirical studies have reported the abilities of audit quality to significantly constrain earnings management [6][7][8] others have reported otherwise.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…While some empirical studies have reported the abilities of audit quality to significantly constrain earnings management [6][7][8] others have reported otherwise.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Ini ditunjukkan dengan aliran kas abnormal yang lebih rendah. Inaam et al (2012) menegaskan bahwa auditor yang memiliki spesialisasi industri mempresentasikan suatu dimensi penting dari kualitas audit. Auditor yang memiliki spesialisasi industri menunjukkan suatu dimensi penting kualitas audit.…”
Section: Auditor Eksternal Dan Manajemen Labaunclassified
“…Auditor lebih mudah untuk mengetahui akrual ini. Hasil penelitian ini konsisten dengan hasil penelitian yang dilakukan oleh Inaam et al (2012) yang menemukan bahwa auditor berkualitas tidak mampu mencegah praktik manajemen aktivitas riil. Ini kemungkinan auditor tidak dapat memainkan perannya untuk mengurangi manipulasi aktivitas riil karena manipulasi ini lebih sulit bagi auditor eksternal, regulator, dan stakeholder lain untuk mendeteksi manipulasi aktivitas riil dibanding manajemen laba akrual.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Burnett et al (2012) find that when the financial reports are audited by high quality auditor, the managers tend to swap the accrual based EM with real EM. Similarly, Inaam et al (2012) demonstrate that auditor industry specialization negatively effects accrual based EM. Sun and Liu (2013) suggest that the auditor industry specialization complements board independence in the governance process.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 90%